Робітництво Миколаєва: економічне становище та соціальна боротьба напередодні і в ході Першої російської революції - Бобіна, О. (Краєзнавство, 2018)
Соціальна боротьба невід'ємна і складова частина соціального життя. Активний соціальний рух робітників м. Миколаєва починається в 1903–1905 рр. Ця боротьба носила економічний характер. Політичний елемент соціальної боротьби не відігравав великої ролі. Радикальні партії в Миколаєві були слабкими, і кадрово, і організаційно. Партії не змогли повністю підкорити рух робітників. Незважаючи на це боротьба миколаївського робітництва стала складовою частиною першої загальноросійської революції початку ХХ ст. Social struggle in the integral characteristics of capitalism. Social struggle is an integral and component part of the social life. The workers of two Mykolaiv plants have made their contribution to the history of social struggle in Ukraine in the end of the XIX century – the beginning of the XX century. The active social movement of the working people in Mykolayiv (Ukraine) started in 1903–1905. Mostly, this social struggle had economic nature and the political component of this struggle was not of great importance. The radical parties in Mykolayiv were weak both in professional and organizational ways. These parties were not able to bring the working class movement under their control. In spite of this fact, the struggle of the Mykolayiv working people became an integral part of the first Russian revolution in the 20th century. Социальная борьба неотъемлемая и составляющая часть социальной жизни. Активное социальное движение рабочих г. Николаева (Украина) начинается в 1903–1905 гг. Эта социальная борьба носит, прежде всего, экономический характер. Политический компонент этой борьбы не имел большого значения. Радикальные партии в Николаеве были слабыми, и профессионально, и организационно. Эти партии не смогли полностью подчинить себе рабочее движение. Несмотря на это борьба николаевских рабочих стала составной частью первой российской революции ХХ в.